THE ASIATIC SPECIES OF LINDENBERGIA Lehm. (Scrophulariaceae) - B. PRIJANTO* (REINWARDTIA, 1969)
Lindenbergia is represented in Asia by 7 species. Based on the hairiness of their ovaries L. muraria (Roxb.) Briihl (= L. urticifolia Lehm.) and L. indica (L.) Vatke (= L. polyantha Benth.) are reinstated as distinct species. I follow Bentham in including Lindenbergia in the tribe Gratioleae. Objection to the use of the aestivation of corolla as the only positive character for distinguishing subfamilies of the Scrophulariaceae is put forward; it is shown that several genera (Lindenbergia, Isoplexis, Lagotis, Erinus, Freylinia,, Phygelius and Mimulus) considered to belong to one subfamily actually have the aestivation character of the other subfamily. The occurrence of resupinatton of the flower in Dopatrium juncewm (Roxb.) Buch.-Ham. ex Benth. is recorded for the first time.